(untitled) (International Journal of Engineering and Computer Science, 2014)
Image enhancement is a region of improving the visual clarity of the image in digital image processing. In this paper, we propose a new algorithm using CLAHE and unsharp masking with bilateral filter. Enhancement of contrast and sharpness of an image is required in many applications. In applications like medical radiography enhancing movie features and observing the planets it is necessary to enhance the contrast and sharpness of an image. Unsharp masking is good tool for sharpness enhancement; it is an anti-blurring filter. By using unsharp masking algorithm for sharpness enhancement, the resultant image suffering with two problems, first one is a hallo is appear around the edges of an image, and second one is rescaling process is needed for the resultant image. The aim of this paper is to enhance the contrast and sharpness of an image simultaneously and to solve the problems. In the proposed algorithm, we can adjust the two parameters controlling the contrast and sharpness to produce the desired output.